Análise e síntese de redes de microcavidades em anel utilizando a teoria de modos acoplados com uma abordagem por grafos de fluxo de sinal - Brigante, Daniel Amaral (Universidade Federal de São Carlos, 2025)
This work presents a formalism based on two-port network theory for modeling filters composed of ring-shaped microcavities applied to integrated photonic circuits. As an equivalent alternative to the conventional matrix-based approach, signal-flow graph theory is employed to provide a graphical representation of the different device sections and their interactions. A direct connection between the graph-based description of cascaded network associations and the definition of the Redheffer star product is established. Coupled-mode theory is introduced to characterize the network parameters of the devices. Based on the signal-flow graph representation of time-domain coupled-mode equations, a methodology for the synthesis of cascaded coupled-cavity filters is presented, with application to a second-order Butterworth filter. The results are validated through numerical simulations using the finite-difference time-domain method, demonstrating the consistency of the proposed procedure.
Analysis and synthesis of ring microcavity networks using coupled-mode theory with a signal-flow graph approach
Keywords: Fotônica integrada; Microcavidades em anel; Teoria de modos acoplados; Redes de duas portas; Grafos de fluxo de sinal; Síntese de filtros fotônicos; ENGENHARIAS::ENGENHARIA ELETRICA::TELECOMUNICACOES; 4. Educação de Qualidade; 9. Indústria, Inovação e Infraestrutura